The Miraculous Antioxidant Fig in The Quran Exploring its Quranic Uslūb and Profound Significance - Nurul Mukminah Zainan Nazri; Nurul Jannah Zainan Nazri; Mohd Arif Nazri (Nungemilang Enterprise, 2024)
Indexed by MyCite